Thinning the Bulk into the Soft: Flexible and Stretchable Germanium Photodetectors - Guopeng Zhao; Qinglei Guo (Advanced Materials Interfaces, 2024)
Abstract Inorganic semiconductor‐based nano/micro‐membranes are of great interest and can be used as active materials for high‐performance and flexible electronics, due to their unique and stable physical or chemical properties. However, the creation of high‐quality and single‐crystalline semiconducting membranes, particularly germanium (Ge) membranes, remains a significant challenge. In this study, a wet etching approach is developed to thin bulk Ge into soft Ge membranes, which are further used to fabricate flexible and stretchable photodetectors. The thickness of the obtained Ge membranes can be precisely controlled, with a minimum thickness of ≈1.6 µm. Investigations on the surface morphology, surface chemical composition, and Raman shifts indicate that the prepared Ge membranes are single‐crystalline and suitable for the following device fabrication. As an example, flexible and stretchable Ge photodetectors, of which the stretchability is realized by a meshed‐structure design, are demonstrated. Bending (with a minimum radius of 4 mm and a bending cycle of 10 000 times) and stretching (with a stretching strain of up to 10%) tests result in negligible variations in the device performance, revealing good flexibility, and stretchability, as well as the significant potentials of the prepared Ge membranes as candidates for flexible electronics.